Immersive Quantum Phenomena Laboratories: Principle of Light and Polarization - Rafael Bulcão; Henrique Sobrinho Ghizoni; Fernando Vieira Mascarenhas; Rafael Rodrigues Cezimbra; Yasmim Thasla; Anderson Correia Buarque; Ingrid Winkler (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
Teaching quantum physics concepts and phenomena can be facilitated through experimental practices. However, these practices are often costly and require dedicated space, making them unfeasible for low-resource educational institutions. Given these limitations, the use of virtual and augmented reality technology has emerged as an intermediary mechanism and teaching resource for quantum physics teaching. This study presents the preliminary development of the designed artifact and the applicability of an immersive laboratory to demonstrate the phenomena of polarization and the principle of light. This research follows the design science research (DSR) approach, proposing the initial development of the artifact and indicating its applicability as a quantum physics teaching tool, specifically for quantum optics phenomena. The proof-of-concept was developed within the UNITY engine and tested with the Meta Quest 3 and 3s headsets. As a result, an immersive, interactive, and functional environment was created for testing, evaluation, and use as a teaching tool. This work contributes to the development of a mobile and reusable teaching laboratory, proposing innovation in the educational path of quantum technologies.